IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP KESEJAHTERAAN MASYARAKAT SEKITAR PADA PT. VALE INDONESIA Tbk - Rasdiah Rasyid (Jurnal Bisnis dan Kewirausahaan, 2015)
This research aims to know and analized The influence of Corporate Social Responsibilty Implementation for the Public Welfare about PT Vale Indonesia. These research applied in surroundings PT Vale Indonesia. A sample of using methods purposive of sampling. A method of data used is live interview to the many involved in the problem under discussion and give a questionnaire for employees according to research conducted. Data analysis was done using multiple linear regression analysis, test T test, test F test and The coefficient of determination (R2). The results of an analysis of shows that the Corporate Social Responsibilty Implementation it has positive infleunced and significant to Public Welfare about PT Vale Indonesia.